Analysis of the Determinants of Foreign Direct Investment Attractiveness in the Industrial Sector in Tunisia - Yemmen, Jihene (Journal of Reviews on Global Economics, 2025)
This study aims to assess, using an econometric model based on panel data, the impact of macroeconomic variables on Foreign Direct Investment (FDI) flows in Tunisia’s manufacturing sector. The econometric analysis reveals that factors such as geographic distance, disparities in market size and factor endowments between Tunisia and investor countries, as well as labor availability and competitiveness, are the key determinants of Tunisia’s attractiveness for FDI. These results underscore the importance of structural conditions and comparative advantages in attracting foreign investment to this strategic sector.